IFLA annual 1988 - International Federation of Library Associations and Institutions (München: Verlag Dokumentation Saur, New York, K.G. Saur., 1989)
The IFLA Annual aims to reflect IFLA's activities.
"Proceedings of the General Council. Annual reports."
rpm 23/01/2019
Loans
Keywords: International librarianship; Library science